Linking HPWS, perceived strategic alignment and employee engagement in retail industry - Nguyen Thi, Uyen; Mohamed Zainal, Siti Rohaida (2017)
This paper responses to the emerging call of exploring the role of strategic human resource management as well as its relationship with employee engagement - a “black box” of management in sustaining organizational performance. Strategic HRM is one of very rare concepts of management that are underpinned by the convergence from two of strongest theories in management: RBV and Contingency Theories. It is emerging as one of the most potential Valuable-Rare-Imperfectly imitable- Non substituted resource - VRIN resource that is strongly recommended to be exploited for competitive advantage and sustaining organizational outcomes. However, the study of the effect of strategic HRM which includes two key variables of HPWS and strategic alignment on employee engagement is still unfulfilled gap of research. Especially, in retail industry, the HRM and employee engagement is even more important, because lowest engagement rate often occurs in this industry and several studies asserted the special role of employee engagement in sustaining retail performance due to its epidemic influence on customers. Thus, this paper bridges this gap by justifying the nature of strategic HRM from the perspectives of 2 key components including HPWS and strategic alignment and exploring its potential effect on employee engagement in retail industry. The proposed conceptual model and generated propositions in this study will enrich the cross-field of strategic HRM and provide guidance for further empirical studies in retail context.